Predictive Capacity of Different Indicators of Adiposity for Metabolic Syndrome in Adults in the City of Trujillo, Peru - Jorge Luis Díaz-Ortega; Joao Caballero-Vidal; Irma Luz Yupari-Azabache; Juan M. Alva Sevilla; Nelson Enrique Conde-Parada (Medicina)
Background and Objectives: Various adiposity indicators have been used to predict metabolic syndrome (MetS). The aim of the present study was to evaluate the predictive ability of known adiposity indicators, such as abdominal girth, girth/height and fat percentage, as well as less commonly used indicators, such as the conicity index (CI), body roundness index (BRI), visceral adiposity index (VAI) and body shape index (ABSI), to predict MetS. Materials and Methods: A total of 261 participants, including family members and graduates of a flagship school in the city of Trujillo, Peru, participated. Metabolic syndrome was assessed according to the harmonised ATP III criteria. ROC curves were analysed for each of the adiposity indicators using SPSS 26.0 statistical software. Results: The prevalence of MetS was found to be 43.4%, with a higher proportion in men (25.8%). The area under the curve (AUC) for the prediction of MetS exceeded a value of 0.8 for VAI, abdominal circumference, circumference/height and relative fat mass in both men and women, with VAI showing the highest values of 0.858 and 0.875 in women and men, with cut-off points for MetS of 2.57 and 1.73, respectively. Conclusions: VAI can be used in the diagnosis of metabolic syndrome during lipid profile and anthropometric assessment.